2011
DOI: 10.3851/imp1890
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Carraguard, a Vaginal Microbicide, in Protecting Women against High-Risk Human Papillomavirus Infection

Abstract: The prevalence of HR-HPV infection was lower in compliant Carraguard users than compliant placebo users. To our knowledge, this is the first report showing a negative association of HPV infection with a vaginal microbicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 13 publications
1
62
0
Order By: Relevance
“…It has been shown to be safe and acceptable in numerous preclinical and clinical studies (7,19,22,(25)(26)(27)(28)(29)(30)(31)(32) despite contradictory observations using in vitro systems that CG can enhance HIV infection (22,33). Additionally, CG may have activity against HPV (34)(35)(36). Because the 14 mM ZA formulation (but not lower concentrations) afforded efficacy comparable to that of the 23 mM ZA formulation in mice (7), we advanced the 14 mM ZA/CG gel for macaque testing.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be safe and acceptable in numerous preclinical and clinical studies (7,19,22,(25)(26)(27)(28)(29)(30)(31)(32) despite contradictory observations using in vitro systems that CG can enhance HIV infection (22,33). Additionally, CG may have activity against HPV (34)(35)(36). Because the 14 mM ZA formulation (but not lower concentrations) afforded efficacy comparable to that of the 23 mM ZA formulation in mice (7), we advanced the 14 mM ZA/CG gel for macaque testing.…”
Section: Discussionmentioning
confidence: 99%
“…CG gels were also potent inhibitors of cervicovaginal infection in mouse and rhesus macaque models [22, 27, 28]. In a clinical trial of a CG-based microbicide primarily directed at HIV prevention, there were one-third fewer genital HPV infections detected at study exit in the most adherent subgroup of women, compared to controls [38]. Two randomized placebo controlled clinical trials evaluating a commercial CG-based product, Divine #9, as a topical microbicide to specifically prevent genital HPV infection in young women are now underway.…”
Section: Hpv Prevention Strategies: Learning From Success and Moving mentioning
confidence: 99%
“…It has been shown to prevent human papillomavirus (HPV) infection in mice (43), while closer analysis of a subgroup of highly adherent subjects in the Carraguard phase 3 clinical trial suggested that the carrageenan gel reduced the prevalence of HPV (34). Carrageenan-based gels have been shown to prevent significant HSV-2 infection in the HSV-2 mouse model when challenged with low viral doses of HSV-2 (30,32,53).…”
mentioning
confidence: 99%